The Influence of The Contextual Teaching and Learning (CTL) Learning Model on Student Learning Outcomes in Subtema 3 Animal Growth in Class III UPTD SDN 122365 Pematang Siantar - Dina Ria Christina Sinambela; Natalina Purba; Lisbet Novianti Sihombing (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of the contextual teaching and learning (CTL) learning model on student learning outcomes in subtheme 3 animal growth in class III UPTD SD Negeri 122365 Pematang Siantar. The method in this research is a quantitative experimental type method whose research design is pre- experimental type one group pretest-posttest . The population and sample used were saturated sampling with 22 samples, as well as two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of the Contextual Teaching and Learning model. The data collection technique is the test technique. The test results using the t-test technique with the help of the spss program, based on the calculation results obtained tcount = 22.894 with a significance level (2-tailed) 0.000, significant probability < 0.005, tcount > ttable = 22.894 > 2.064, so H0 is rejected and Ha is accepted. This explanation shows that there is an influence of the Contextual Teaching and Learning (CTL) Model on the learning outcomes of class III students in Subtheme 3 at SD Negeri 122365 Rambung Pematang Siantar.